Autofocus methods of whole slide imaging systems and the introduction of a second-generation independent dual sensor scanning method - Michael C Montalto; Richard R McKay; Robert J Filkins (Elsevier, 2011)
Accurate focusing is a critical challenge of whole slide imaging, primarily due to inherent tissue topography variability. Traditional line scanning and tile-based scanning systems are limited in their ability to acquire a high degree of focus points while still maintaining high throughput. This review examines limitations with first-generation whole slide scanning systems and explores a novel approach that employs continuous autofocus, referred to as independent dual sensor scanning. This "second-generation" concept decouples image acquisition from focusing, allowing for rapid scanning while maintaining continuous accurate focus. The technical concepts, merits, and limitations of this method are explained and compared to that of a traditional whole slide scanning system.